The Epidemiology of Methicillin-Resistant Staphylococcus aureus (MRSA) in Germany - Köck, Robin (Deutscher Arzte Verlag, 2011)
BACKGROUND: For decades, methicillin-resistant Staphylococcus aureus (MRSA) has been a major cause of infection in hospitals and nursing homes (health care-associated MRSA, HA-MRSA). Beginning in the late 1990s, many countries have also experienced a rising incidence of MRSA infection outside of the health care setting (community-associated MRSA, CA-MRSA). Moreover, animal reservoirs are increasingly considered to represent an important source of human MRSA acquisition. In this review article the authors describe the current epidemiological situation of MRSA in Germany. METHODS: This review is based on pertinent articles published up to 2010 that were retrieved by a selective PubMed search, as well as on publications issued by national reference institutions up to 2010. RESULTS: There are about 132 000 cases of MRSA in German hospitals each year. MRSA is found in about 18% to 20% of all inpatient-derived culture specimens that are positive for S. aureus. CA-MRSA is not yet endemic in Germany; important risk factors for its acquisition include travel to high-prevalence areas and household contact with persons that harbor a CA-MRSA infection. Agricultural livestock is the main animal reservoir for MRSA, which is often zoonotically transmitted from animals to human beings by direct contact. However, both CA-MRSA and MRSA from animal reservoirs can be imported into hospitals and cause nosocomial infections. CONCLUSION: Hospitals and nursing homes were once the main reservoirs of MRSA, but new ones have now emerged outside of the healthcare setting. Efforts to prevent MRSA and limit its spread must rise to this new challenge.